Technique Real Time Ultrasonography Imaging With MRI or CT Scan Using Fusion Imaging (Hybrid Imaging) - Giovana Nopa Prancisca (Journal of Applied Health Management and Technology, 2022)
ABSTRAKIntroduction : Ultrasound examination (USG) is a modality that is real time, fast, has high resolution, and is dynamic, but ultrasound has shortcomings in displaying the anatomical context presented by CT and MRI, therefore fusion imaging connects several imaging modalities (hybrid imaging) between real time ultrasound, CT and MRI which are useful in providing anatomical information that help each other, besides that it can also be used for biopsy. Case Illustration: In real time ultrasound imaging, the author uses the Phillips brand ultrasound modality with a premium class Epiq 5 type which is equipped with Percunav imaging software and prepared equipment such as a transmitter, patient tracker, Ultrasound tracker (sensor bracket) and the probe used is Convex 5-1 .Discussion: We can see the focal nodule contour in real time with hybrid imaging, and we can compare the diameter of the lesion between the two modalities. In addition, with realtime ultrasound, we can see metastases by looking at vascularization using Doppler. Conclusion: In this 4.0 era, fusion imaging (hybrid imaging) plays a very important role in diagnosis, staging and follow-up during treatment. Fusion imaging allows good control during the review of liver lesions so that no re-exposure to radiation is used.